2016
DOI: 10.1002/2016gl067938
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐linear simulations of inner radiation belt electron pitch angle and energy distributions

Abstract: “Peculiar” or “butterfly” electron pitch angle distributions (PADs), with minima near 90°, have recently been observed in the inner radiation belt. These electrons are traditionally treated by pure pitch angle diffusion, driven by plasmaspheric hiss, lightning‐generated whistlers, and VLF transmitter signals. Since this leads to monotonic PADs, energy diffusion by magnetosonic waves has been proposed to account for the observations. We show that the observed PADs arise readily from two‐dimensional diffusion at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 48 publications
6
93
0
Order By: Relevance
“…Mourenas et al () also found MS waves with relatively smaller wave normal angle are more favorable for scattering electrons from the analyses of Quasi‐linear theory (QLT), which is another widely used method to study MS wave‐particle interaction (e.g., Horne et al, ; Ma et al, ). Moreover, the scattering effect is very sensitive to the wave normal angle, which is consistent with the results of Albert () and Albert et al (). The reason for the sensitivity lies in the fact that the resonance velocity v res = ω / k cos φ changes sharply as φ approaches 90°, while the overall phase velocity of ω / k remains almost unchanged.…”
Section: Parametric Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Mourenas et al () also found MS waves with relatively smaller wave normal angle are more favorable for scattering electrons from the analyses of Quasi‐linear theory (QLT), which is another widely used method to study MS wave‐particle interaction (e.g., Horne et al, ; Ma et al, ). Moreover, the scattering effect is very sensitive to the wave normal angle, which is consistent with the results of Albert () and Albert et al (). The reason for the sensitivity lies in the fact that the resonance velocity v res = ω / k cos φ changes sharply as φ approaches 90°, while the overall phase velocity of ω / k remains almost unchanged.…”
Section: Parametric Studysupporting
confidence: 91%
“…As shown in Figure h, butterfly distribution is produced from the very beginning inside the plasmapause, which means MS waves accelerate and scatter 90° electrons directly. This mechanism has been interpreted as parallel acceleration due to Landau resonance (Li, Ni, et al, ) or, equivalently, the negative cross diffusion coefficients (Albert et al, ). Outside the plasmapause, as shown in Figure i, the MS waves scatter medium pitch angle electrons and produce a slot at around 80° pitch angles in the first few hours.…”
Section: Electron Diffusion Simulationmentioning
confidence: 99%
“…Finally, Figures shows the great diversity of solutions obtained according to the choice of models (both D LL and τ ), which argues in favor of more simulations (for different events) to confirm the findings of the current study. The good reproduction of the flux decay with the lifetime of this study gives also confidence in the pitch angle diffusion coefficients and a future capability to simulate finer effects with these coefficients used within a 3‐D Fokker‐Planck framework [e.g., Tu et al , ; Drozdov et al , ], such as, for instance, the formation of butterfly pitch angle distributions distribution [ Zhao et al , , ; Albert et al , ] and pitch angle dependent loss [e.g., Yu et al , ].…”
Section: Validation With Van Allen Probes Observationsmentioning
confidence: 80%
“…Hiss waves interact with tens to hundreds of keV electrons, causing electron pitch angle scattering and precipitation of Earth's radiation belt electrons into the upper atmosphere [Abel and Thorne, 1998;Horne and Thorne, 1998;Shprits et al, 2008;Ni et al, 2013Ni et al, , 2014]. In addition, Landau resonance due to hiss waves affects the energetic electrons at high pitch angles (close to 90°) or at energies slightly lower than the electron cyclotron resonance energy, which may contribute to the formation of "butterfly" pitch angle distribution in the inner radiation belt [Albert et al, 2016]. The pitch angle scattering due to the combined effect of cyclotron and Landau resonance effects leads to the typical "top-hat"-shaped pitch angle distribution of tens to hundreds of keV electrons and the flattened pitch angle distribution at higher energies up to several MeV in the outer radiation belt [Ni et al, 2013].…”
Section: Introductionmentioning
confidence: 99%